Treatment of polycystic ovarian syndrome in primary care. Issue 11 (November 2016) - Graham, Anna; Hamoda, Haitham
Abstract : Polycystic ovarian syndrome (PCOS) is a common and complex syndrome that presents with a wide spectrum of clinical symptoms and is also associated with several other serious conditions. This article reviews the recommended management of PCOS and its associated symptoms in primary care and discusses when referral is necessary.